Young People's Coping Strategies Concerning Climate Change: Relations to Perceived Communication With Parents and Friends and Proenvironmental Behavior. Issue 8 (October 2019) - Ojala, Maria; Bengtsson, Hans
Taking its departure in the transactional theory of coping and socialization theories, this questionnaire study investigates how coping with climate change among late adolescents ( N = 705) relates to proenvironmental behavior and communication with significant others about societal problems. Deemphasizing the problem was negatively associated with proenvironmental behavior, whereas problem-focused and meaning-focused coping were positively associated with proenvironmental behavior. Two communication patterns with fathers, mothers, and friends were identified: one solution oriented and supportive, and one dismissive and doom-and-gloom oriented. The positive patterns correlated positively with problem-focused and meaning-focused coping, whereas the negative patterns correlated positively with deemphasizing. Communication with fathers was particularly important in explaining deemphasizing and problem-focused coping. A structural equation modeling (SEM) analysis showed that coping mediates the effects of communication patterns on behavior, whereas problem-focused coping mediates the influence of other coping strategies on behavior. The study demonstrates the importance of considering coping as a factor in the socialization of proenvironmental behavior.